Behavioral responses to anthropogenic noise at highways vary across temporal scales - Collins, Amy C.; Vickers, T. Winston; Shilling, Fraser M. (Frontiers in Ecology and Evolution, 2022)
Anthropogenic noise is pervasive across the landscape and can be present at two temporal scales: acute (occurring sporadically and stochastically over the shortest time scales e.g., milliseconds), and chronic (more persistent than instantaneous and occurring over longer timescales e.g., minutes, days). Acute and chronic anthropogenic noise may induce a behavioral fear-mediated response in wildlife that is analogous to a prey response to predators. Understanding wildlife responses to anthropogenic noise is especially important in the case of wildlife crossing structures that provide wildlife with access to resources across busy roadways. Focusing on two species common at wildlife crossing structures, mule deer (Odocoileus hemionus) and coyotes (Canis latrans), we addressed the hypotheses that 1) acute traffic noise causes flight behavior; and 2) chronic traffic noise causes changes in a range of behaviors associated with the vigilance - foraging trade-off (vigilance, running, foraging). We placed camera traps at entrances to ten crossing structures for a period of ~ two months each throughout California, USA. Mule deer and coyotes demonstrated a flight response to acute traffic noise at entrances to crossing structures. Both species demonstrated shifts in behavioral response to chronic traffic noise within and among structures. Coyote behavior was indicative of fear, demonstrating increased vigilance at louder times within crossing structures, and switching from vigilance to running activity at louder crossings. Mule deer responded positively, increasing foraging at both spatial scales, and demonstrating decreased vigilance at louder structures, potentially using crossing structures as a Human Shield. Our results are the first to demonstrate that anthropogenic noise at crossing structures could alter wildlife passage, and that variations in fear response to anthropogenic noise exist across temporal, spatial and amplitude scales. This dynamic response could alter natural predator-prey interactions and scale up to ecosystem-level consequences such as trophic cascades in areas with roads.